Acute effect of erythromycin on metabolic transformations of volatile fatty acid mixture under anaerobic conditions. (April 2015) - Cetecioglu, Z.; Ince, B.; Ince, O.; Orhon, D.
Highlights: At lower doses, VFA mixture was completely removed but partially utilized for biogas. At higher doses, propionate utilization was impaired with reduced butyrate removal. Remaining VFAs were partly converted to new VFA isomers and polymers. High erythromycin doses induced total inactivation of microbial metabolism. Abstract: The study explored the acute inhibitory impact of erythromycin on the methanogenic activity of acclimated biomass fed with a volatile fatty acid mixture and acetate alone. Parallel batch reactors were operated for six days, with increasing erythromycin dosing in the range of 1–1000 mg L −1 . Substrate removal was monitored by means of soluble COD and volatile fatty acid (VFA) measurements together with parallel observations on biogas and methane generation. The inhibitory impact was variable with the initial erythromycin dose: At lower doses, the VFA mixture was completely removed but partially utilized, leading to reduced biogas and methane generation, suggesting the analogy of uncompetitive inhibition. At higher doses, propionate utilization was totally impaired and butyrate removal was reduced, but acetate was still fully removed. Remaining VFAs were partly converted to new VFA compound through isomerization and polymerization reactions. High erythromycin doses induced total inactivation of microbial metabolism with negligible methane generation.